(untitled) (Damascus University Journal for legal sciences, 2025)
Investigating the notions of righteousness and perversion and their sub-branches is the most important pillar of Destiny. Thus, most Allah’s prophets and His delivered books concurred that Allah guides through whom he wills and perverts whom he wills. The present research aims to investigate the concepts of Righteousness and Perversion for the Ash’aris and shed some light on some notions in theology to be able to tackle these notions and avoid their misunderstanding. This research also aims to tackle these notions in a scientific manner in their approaches and circumstances. To this end, the researcher sets out to introduce the importance of these terminologies and divides the research into three subsections: The first is searching into the meanings of Righteousness and Perversion in language dictionaries and the signification of the two terminologies in the Holy Quran, in Sunna, for interpreters, and their subdivisions. The second is probing into the Ash’ aris’ notions of Righteousness and Perversion, examining their idiomatic meaning, and investigating what is possible for creation and what is impossible. The third is an analytical study into the Imam Abu-Hasan Al-Ash’ari’s signification of these notions and into the Al-Ash’ari Imams’ doctrine.